Public Engagement as the Fifth Dimension of Outbreak Communication: Public's Perceptions of Public Health Communication during COVID-19 in India. Issue 2 (28th January 2023) - Venkatraman, Krithika; Manoharan, Anand
ABSTRACT: Public health/risk communication is the foremost responsibility of a government during a pandemic. Risk communication aims to educate people, enhance their risk perceptions to help them engage and understand the benefits of compliance with recommendations. The existing legal enforcement of recommendations in India is criticized for failing to influence the public's compliance. While existing research provides conceptual and empirical support in explaining compliance during COVID-19, we note a lack of studies that might bring out country-specific areas of improvement. We argue that value-aligned risk communication is more likely to influence the public's behavioral intentions to adopt the government's recommendations. We employed a triangulation mixed-method study to link risk communication attributes to the public's end goals and values. We triangulate these findings using the COVID score survey. We found that timeliness and transparency constitute risk communication's functional component, and empathy and trust constitute risk communication's emotional component. We found a difference in the preference of functional and emotional components among the public and health partners. Irrespective of this divide in perception, the study found that both groups unanimously noted engagement as the crucial aspect for empowerment and involvement to aid the public in teaming with the government to combat the pandemic effectively.